2019
DOI: 10.1158/1535-7163.mct-18-1151
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the IGF1R/PI3K/AKT Pathway Sensitizes Ewing Sarcoma to BET Bromodomain Inhibitors

Abstract: Inhibitors of the bromodomain and extra-terminal domain (BET) family proteins modulate EWS-FLI1 activities in Ewing sarcoma. However, the efficacy of BET inhibitors as a monotherapy was moderate and transient in preclinical models. The objective of this study was to identify the mechanisms mediating intrinsic resistance to BET inhibitors and develop more effective combination treatments for Ewing sarcoma. Using a panel of Ewing sarcoma cell lines and patient-derived xenograft lines (PDX), we demonstrated that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…We also discovered that IGF1R expression decreased in the calluses of mouse fracture samples with injection of agomiR‐7025‐5p. Previous studies demonstrated that abnormal IGF1R expression plays an important role in the pathogenesis of acute lymphoblastic leukaemia, adrenocortical carcinoma, colorectal cancer and Ewing sarcoma . Thus, our findings indicate that the miR‐7025‐5p/IGF1R axis may play an important role in bone metabolism processes including osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…We also discovered that IGF1R expression decreased in the calluses of mouse fracture samples with injection of agomiR‐7025‐5p. Previous studies demonstrated that abnormal IGF1R expression plays an important role in the pathogenesis of acute lymphoblastic leukaemia, adrenocortical carcinoma, colorectal cancer and Ewing sarcoma . Thus, our findings indicate that the miR‐7025‐5p/IGF1R axis may play an important role in bone metabolism processes including osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 62%
“…This work is also limited by using subcutaneous models. Although subcutaneous tumor models have proven to be useful for evaluating molecular mediators of tumor vasculature and novel therapies for the treatment of ES, the findings reported here should be strengthened using orthotopic ES tumors. Additionally, our studies provided a limited number of days of exercise in a nonvariable fashion with controlled settings on a treadmill.…”
Section: Discussionmentioning
confidence: 91%
“…However, activation of IGF-IR/Akt pathway compromises the efficacy of BET inhibitors in Ewing sarcoma. Combined treatment with BET and IGF-IR pathway inhibitors achieves potent and durable response in preclinical models [139]. Furthermore, the enhancer of zeste homolog (EZH2) is a histone methyltransferase that function as a transcriptional repressor.…”
Section: Molecularly Targeted Therapymentioning
confidence: 99%